Differently literate : boys, girls, and the schooling of literacy - Millard, Elaine (Falmer Press, 1997)
Presents research into the differences in boys' and girls' experiences of the reading and writing curriculum at home and in school. The book includes an outline of the theoretical debates on gender difference and academic achievement.